2001
DOI: 10.1007/s00439-001-0632-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of two mutations in the ABCD1 gene leading to low levels of normal ALDP

Abstract: A variety of mutations have been identified in the X-linked adrenoleukodystrophy (X-ALD) gene, none of which is prevalent. In this work we describe a reverse transcription polymerase chain reaction (RT-PCR)-based strategy specially suited to the molecular characterisation of mutations in index cases. After RT-PCR amplification of the X-ALD transcript a conformation-sensitive gel electrophoresis analysis is performed followed by sequencing of the fragments with altered mobility. Two X-ALD patients were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…We identified 11 variants, including seven new changes, in 12 families. Consistent with data from other groups (Guimaraes et al, 2001), no prevalent mutations were identified. However, the p.Ser514Arg mutation was found in two families who denied formal consanguinity.…”
Section: Discussionsupporting
confidence: 89%
“…We identified 11 variants, including seven new changes, in 12 families. Consistent with data from other groups (Guimaraes et al, 2001), no prevalent mutations were identified. However, the p.Ser514Arg mutation was found in two families who denied formal consanguinity.…”
Section: Discussionsupporting
confidence: 89%
“…The cDNA encoding the human full-length ALDP transporter was amplified by RT-PCR using the F1 and F8 oligonucleotides exactly as described previously (Guimaraes et al 2001) and cloned into the pGEM-T easy vector (Promega). Subsequently, the cDNA was inserted into the EcoRI site of pGEM-4 (Promega).…”
Section: Protease Treatment and Extraction Of Membrane Proteinsmentioning
confidence: 99%
“…Many ABCD1 intronic variants have been identified during diagnostic screening: they account for about 3% of all variants listed at X-ALD database. For the majority of intronic variations, the consequences on mRNA splicing have been only inferred by in-silico analysis, whereas experimental demonstration of their pathogenicity has been obtained by mRNA studies for only few of them (Chiu et al, 2006;Shi et al, 2003;Guimarães et al, 2001Guimarães et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%